TRANSMISSION ELECTRON MICROSCOPY APPLIED TO FLUID INCLUSION INVESTIGATIONS - Viti C.; Frezzotti M.L. (My University, 2001)
The transmission electron microscope (TEM) allows a detailed characterization of textural and chemical features of fluid inclusions (shape, inner compositions and inner textures), at a resolution higher than that attainable with an optical microscope (OM). TEM investigation indicates that most fluid inclusions appear as perfectly euhedral negative crystals, with variable shape (from prismatic to equant) and size (typically from <0.02 to 0.15 μm). Inner texture (fluid phase/melt distribution) and composition are variable as well. Different kinds of negative crystals may coexist in the same trail of inclusions, possibly indicating locally variable trapping conditions.A critical feature, revealed by TEM, is that inclusions are often connected to structural defects (in particular, to dislocation arrays), which are undetected by optical microscopy. The identification of these hidden nanostructures should be taken into account for the correct petrological interpretation of microthermometric results, particularly when controversial data have been obtained. In fact, these nanostructures may represent a possible path for fluid phase leakage, thus modifying the original composition and/or density of the inclusions.
Keywords: TEM; FLUID INCLUSIONS; NEGATIVE CRYSTALS; DISLOCATIONS; LEAKAGE; RE-EQUILIBRATION